A flow cytometric approach to quantify biofilms - Kerstens, Monique; Boulet, Gaëlle; Van Kerckhoven, Marian; Clais, Sofie; Lanckacker, Ellen; Delputte, Peter; Maes, Louis; Cos, Paul (Folia microbiologica, 2015)
Since biofilms are important in many clinical, industrial, and environmental settings, reliable methods to quantify these sessile microbial populations are crucial. Most of the currently available techniques do not allow the enumeration of the viable cell fraction within the biofilm and are often time consuming. This paper proposes flow cytometry (FCM) using the single-stain viability dye TO-PRO(®)-3 iodide as a fast and precise alternative. Mature biofilms of Candida albicans and Escherichia coli were used to optimize biofilm removal and dissociation, as a single-cell suspension is needed for accurate FCM enumeration. To assess the feasibility of FCM quantification of biofilms, E. coli and C. albicans biofilms were analyzed using FCM and crystal violet staining at different time points. A combination of scraping and rinsing proved to be the most efficient technique for biofilm removal. Sonicating for 10 min eliminated the remaining aggregates, resulting in a single-cell suspension. Repeated FCM measurements of biofilm samples revealed a good intraday precision of approximately 5 %. FCM quantification and the crystal violet assay yielded similar biofilm growth curves for both microorganisms, confirming the applicability of our technique. These results show that FCM using TO-PRO(®)-3 iodide as a single-stain viability dye is a valid fast alternative for the quantification of viable cells in a biofilm.
Keywords: Staining and Labeling; Candida; mikrobiologické techniky; Carbocyanines; biofilmy; karbocyaniny; Flow Cytometry; mikrobiální viabilita; Escherichia coli; průtoková cytometrie; Biofilms; Microbial Viability; barvení a značení; Microbiological Techniques